Beliefs About Stress Attenuate the Relation Among Adverse Life Events, Perceived Distress, and Self‐Control. Issue 6 (5th September 2017) - Park, Daeun; Yu, Alisa; Metz, Sarah E.; Tsukayama, Eli; Crum, Alia J.; Duckworth, Angela L.
Abstract : Prior research has shown that adverse events in the lives of adolescents precipitate psychological distress, which in turn impairs self‐control. This study ( N  =   1, 343) examined the protective effects of stress mindsets —beliefs about the extent to which stress might be beneficial or strictly detrimental. The results confirmed that increasing the number of adverse life events across the school year predicted rank order increases in perceived distress, which in turn predicted rank order decreases in self‐control. Adolescents who believed in the potential benefits of stress were less prone to feeling stressed in the wake of adverse life events. These findings suggest that changing the way adolescents think about stress may help protect them from acting impulsively when confronted with adversity.